Blood ordering habits for elective surgery: time for change. - Juma, T (1990)
A prospective study was carried out for 6 months to determine the efficacy of blood ordering routines for elective surgery. It was found that only 23% of procedures needed preoperative crossmatching of blood (transfusion index 'TI' greater than 0.5). There was an excessive over-ordering of blood for 77% of the operations (crossmatch/transfusion ratio greater than 2.5). In addition, the transfusion index for the latter group showed that there was no need to prepare blood preoperatively (TI less than 0.5). A transfusion tariff is worked out which abandons crossmatching for the majority of procedures (cholecystectomy, thyroidectomy and surgery for duodenal ulcer excluding gastrectomy). Instead a 'group and screen' policy is suggested.